PENINGKATAN JIWA KEPEMIMPINAN SISWA MELALUI BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING - Paramita, Suci; Kiswantoro, Arista; Lestari, Indah (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The problem in this study can be formulated as follows: "Is the application of group guidance able to improve the leadership spirit for students of class X SMK N 1 Kalinyamatan Jepara". The objectives of the study were: (1) to describe the leadership spirit of students before and after being given treatment for group guidance services for students of class X SMKN 1 Kalinyamatan, (2) obtaining an increase in leadership spirit through group guidance services for class x SMK N 1 Kalinyamatan students. Research uses: (1) Theoretical Uses; (2) Practical Uses, namely: 1) Principals, can be used to determine policies that can support the effectiveness of the implementation of guidance and counseling in schools, 2) Counselors, can be used by counselors in helping students who lack leadership qualities, 3) Students , Can be used as a guide to change behavior in the future, in order to become a generation that is rich in creativity, firm, superior, and successful in society, 4) Researchers, can be used as reference material and knowledge by researchers related to the provision of group guidance services.